Protest and Parternship: Case Studies of Indigenous Peoples, Consultation and Engagement, and Resource Development in Canada - Jennifer Winter; Brendan Boyd (University of Calgary Press, 2024)
The development of equitable relationships and outcomes among Indigenous communities, resource development companies, and governments in Canada is slow and uneven. Protest and Partnership brings together expert contributors to ask what works—and what doesn't—in these relationships. It explores what processes lead to greater involvement and control in decision-making by Indigenous Peoples and the establishment of mutually beneficial partnerships. Protest and Partnership presents case studies on a range of resource development sectors including oil and gas, renewable energy, mining, and forestry, drawn from regions across Canada. It presents a fine-grained analysis of institutions and processes, demonstrating how Indigenous communities work within and outside frameworks and processes established by governments and industry. It recognizes the persistent failure of Canadian governments to honour treaty rights and provide meaningful consultation and demonstrates how Indigenous groups, communities, and governments have engaged in self-determined resource development despite these ongoing failures. Offering broad lessons in the importance of co-management and co-governance, the autonomy of Indigenous Peoples, transparency and accountability, Indigenous economic security, and meaningful collaboration and engagement, Protest and Partnership is a thorough and careful exploration of the current state of consultation and engagement on resource development with Indigenous communities in Canada.
Keywords: 300; resource development; indigenous rights; indigenous participation; duty to consult; consultation; engagement; resource governance; co-management; impact and benefit; community consultation; co-governance